PENGGUNAAN BAHASA GAUL PADA MEDIA SOSIAL TIKTOK AKUN @ALWANRK EDISI JANUARI-MARET 2024 - Adi Swasono, Bangkit (Universitas Hamzanwadi, 2024)
The phenomenon of using slang can also occur when communicating using technology. One of the technological innovations that is widely used in society is TikTok. The purpose of this study is to obtain a description of the use of spoken slang in video posts and to obtain a description of the use of written slang in the comments column. This study uses a descriptive qualitative method to see what types of slang are in the @alwanrk account. The researcher used a data collection method in the form of documents that had been taken from TikTok by understanding the contents of the @alwanrk account and then concluding from the results of use on the @alwanrk account. The data obtained amounted to 28 spoken data in the form of 13 acronym data, 3 abbreviation data, and 12 contraction data, while there were 56 written data in the form of 16 acronym data, 17 abbreviation data, and 23 contraction data. The existing data serves as a basis for classifying the types of slang words used in the @alwanrk account.